ORÇAMENTO POR DESEMPENHO: UMA ANÁLISE DA RELAÇÃO ENTRE DESEMPENHO E ALOCAÇÃO DE RECURSOS EM AÇÕES NO ORÇAMENTO DE UMA INSTITUIÇÃO FEDERAL DE ENSINO SUPERIOR - Maurício Vasconcellos Leão Lyrio (Universidade Federal de Santa Catarina, 2014)
This article is located in the discussion of allocation of public resources, specifically in the context of a Federal Higher Education Institution - IFES - which in this case is the object of study. From a discomfort on the part of the authors regarding the use of performance information in budgeting of the Federal University of Santa Catarina - UFSC it aims to answer the following research question: Is there a positive correlation between the achieved performance indicators and the resources allocated to budget actions under the Federal University of Santa Catarina? To achieve its goal, the authors follow a line of research that appears in alignment with the so called movement for results which began with the fiscal crisis of the 1980s, namely, Performance-based Budgeting - PBB - or budget for results or performance. With regard to the study methodology it is framed as descriptive, adopting a quantitative approach and using descriptive statistics to analyze the data. The results demonstrated a weak correlation between the performance of the actions of the analyzed institution's budget and the resources allocated to these actions.